Corridor development and rural transformation: A comparative study of Delhi - Choubey, Narayan Awadh and Bansal, Taruna (Nagalok)
In the 1940s the United Nations in their statistical reports adopted the categorization of areas into either rural or urban. This approach was based on the premise that to understand the social, economic, political, cultural and demographic processes one has to consider the place where human beings live and work. The most basic within the settlement system of human beings. In recent decades, this categorization has lost its importance as massive changes have occurred in the size, spatial extent, nature and morphology of the settlements. In fact there is no clear dividing line between the rural and urban settlement and their dwellers. These two have intertwined in such a manner that instead of being isolated settlements they have become dependent on each other. - Reproduced
Keywords: Urban Corridors